Intelligent Classification of the Abnormal Features through Time-Delayed Reconstruction of Phase States - Yu, Wen; Wang, Tianfeng; Xu, Yeyin (Journal of Applied Nonlinear Dynamics, 2026)
Epilepsy is a common brain disease in the world, and its clinical diagnosis has always been essential in epilepsy treatment. However, the current medical practice mainly relies on the patient's clinical symptoms and the doctor's manual judgment based on electroencephalogram(EEG), which has significant shortcomings in efficiency and accuracy. With the development of machine learning, artificial intelligence is used for the diagnosis of epileptic seizures in practice. In this paper, we established two different input features: only power spectral density (PSD) and recurrence rate (RR) combined with PSD. Such recurrence rate is achieved through the phase state reconstruction of the time-delayed signals. Considering the recursive characteristics, the accuracy for diagnosing epileptic seizures can reach to 99%. We also compared the performance of the two types of input data and discussed the scale of input data on the results. The influence of time-delay parameters in the recurrence rate is studied. The result shows that the diagnosis through power spectral density with recursive rate as dataset is better than that of judging only by power spectral density. By considering the recurrence rate, the intelligent diagnosis accuracy of the neural network improves by varying degrees, ranging from 0.3% to 1.5%, depending on the size of the input data. The specificity of the neural network improves by varying degrees, ranging from 0.2% to 3.4%, depending on the size of the input data. Simultaneously, the sensitivity values also have risen, ranging from 0.1% to 1.7%. With the increase of data scale, the convergence speed of the neural network in earlier iteration stage will be accelerated. In Fig.10 (c) and (d), considering both RR and PSD results in achieving an accuracy of 98% after only 32 iterations, which is comparable to the accuracy achieved after 186 iterations when only considering PSD. In Fig.11 (a) and (b), the curve of 400 PSD with or without RR is the fastest descending curve in their series, which reflects that the convergence speed accelerates as dataset size increases. However, when the data volume gets larger, the CNN network needs more iteration epochs to achieve stable. That's why there is more fluctuation in curve of 400 PSD with or without RR. The research provides a good perspective for clinical diagnosis of epilepsy seizures.